Improvement the elevated performance of LiMn2O4 electrode by nano-CeO2 modification on the surface - Liu, Zhuangzhuang; Zhang, Yichi; Jiang, Qianqian; JianguoTang (Ionics, 2022)
Homogeneous nano-CeO 2 coated on LiMn 2 O 4 powder has been successfully prepared via a facile solid-state approach. Our work demonstrates that surface modification of LiMn 2 O 4 sintered at 450 °C shows a high initial discharge of 137.7 mAh·g −1 and superior capacity retention with 95.86%, which is much higher that of the pristine LiMn 2 O 4 . In addition, CeO 2 @LMO-450 has excellent rate performance especially at elevated performance, probably due to the faster Li + transportation and the improvement of the electrical conductivity by nano-CeO 2 layer. When cycled at 0.2 C between 3.0 and 4.3 V at 60 °C, CeO 2 @LMO-450 shows discharge capacity of 116.1 mAh·g −1 after 60 cycles with a capacity retention of 88.36%, which is two times more than that of pristine LiMn 2 O 4 . The improvement of the electrochemical performance of LiMn 2 O 4 by nano-CeO 2 layer surface modification can suppress the dissolution reaction of manganese ions, even at elevated temperature, and clearly improve the cyclability of spinel LiMn 2 O 4 .